Complex assessment of structural systems used for high-rise buildings - Tamošaitienė, Jolanta; Gaudutis, Ernestas (Journal of Civil Engineering and Management, 2013)
Today, increasingly more attention is given to reduction of the negative impacts of human activities on the surrounding environment during different stages of a building life cycle, which should be estimated during the design stage of the building. Selection of a structural system for a high-rise building remains a complex task that requires estimating a large amount of data such as structural system parameters, architectural solutions, engineering system requirements and construction process peculiarities. Decision-making problems in civil engineering often involve a complex decision-making process, in which multiple requirements and conditions have to be taken into consideration simultaneously. It means that such problems deal with sets of multiple criteria. The accuracy of performance measures in COPRAS (COmplex PRoportional ASsessment) method assumes direct and proportional dependence of the significance and utility degree of investigated alternatives on a system of criteria adequately describing the alternatives as well as on values and weights of the criteria. The research has concluded that the COPRAS-G method is appropriate for assessment of structural systems of high-rise buildings.